Prevalence of Depression in Diabetic Patients Type 2 - Sahib, Dr. Adil Jafaar Abdul (International Journal of Psychosocial Rehabilitation, 2020)
--- Background: Diabetes mellitus (DM) is one of the commonest disease in the world, it leads to inability and to many fatal complications if left without good treatment, good care delays the appearance of complications , improves the quality of life and reduces the cost of treatment, It has become known that there is an increase in the prevalence of depression in diabetics and this accompanying depression leads to the deterioration in the quality of life for these patients.Aims: To study the prevalence of depression in people with type 2 diabetes and its effect on controlling blood sugar and the quality of life.Settings and Design: One diabetes center, one cross-sectional study, one interviewMaterials and Methods: A group consisting of 80 patients with type 2 diabetes is included in this study. In order to diagnose depression, the DSM 5 diagnostic criteria for depressive episode (Arabic) was used. All patients were interviewed using a semi-structured form to assess Sociodemographic data, "Hamilton Rating Scale for Depression (HAM-D)” and “Quality of Life Enjoyment and Satisfaction Questionnaire (Q-LES–Q) SF” (Short Form) to measure the quality of life.Conclusion: This study concluded that the presence of depression in patients with type 2 diabetes leads to a deterioration in the quality of life. Therefore, treatment of depression will lead to an improvement in the quality of life.